Relationship between family attachment and resilience among secondary school students abusing mitragya speciosa (ketum, kratom or kratom) - Shaari, Azemi (Serials Publications, 2016)
This study seek to investigate relationship between family attachment and resilience among secondary students abusing Mitragyna Speciosa (ketum, Kratom or kratum). Using quantitative correlational study research methods. The whole population of 200 students from 42 secondary schools in the district of Kubang Pasu states of Kedah, Malaysia were chosen as research sampel based from school diciplinary report abusing Mitragyna Speciosa. Two sets of instruments used to measured resilience and parental attachment, The Resilliency Questionnaire (RQ) by the Jew, Green and Kroger (1999); Mohd Nasir (2006) and Mohd Saper (2014) with .65 cronbach alpha value of realiability and Inventory of Parental Attachment (IPA), by Kenny and Rice (1995): Noriah Ishak (1999) and Azemi Shaari (2014) with .882 65 cronbach alpha value of realiability. Reseach results based on the pearson (r) correlation test showed that significant relationship between family attachment and resilience among secondary school students taking Mitragyna Speciosa r = 0.389; p <0.05 and r = 0.237 father; <0.05. This research result showed that increasing in family attachment will increase resilence among secondary school students abusing Mitragyna Speciosa.An overall results from this research showed that increasing in family attachment were correlated with increases in resilience among secondary school students abusing Mitragyna Speciosa. Family attachment is an important role in building resilience among school children from abusing Mitragyna Speciosa.